The Effects of Vitamins on Micropropagation of Desiree and Mozart Potatoes (Solanum Tuberosum L.) - Fareed K. Yaseen; Rafail S. Toma; Daniela Carbonera (Science Journal of University of Zakho, 2017)
An attempt was done to achieve a micropropagation protocol by determining the most optimal types and concentrations of vitamins including thiamine (B1), nicotinic acid (B3), pyridoxine (B6) and folic acid to induce shoot formation and rooting in vitro, as replacement vitamins in the culture medium. The four vitamins were included in the medium at two concentrations and the control treatment without vitamins. The highest number of shoots per explant (2.50 shoots/ explant) was achieved from the addition of 0.3 mgl-1thiamin to Desiree cultivar grown on MS medium. Whereas, the highest mean length of shoots was recorded in the case of adding nicotinic acid at 3.0 mgl-1 to Mozart cultivar grown on MS medium. The highest number of leaves 10.50 leaves/ explant) was obtained from Mozart cultivar grown on a medium enriched with 0.6 mgl-1 pyridoxine. The highest number of roots (7.00 roots/ explant) was achieved from the control treatment from Desiree potato cultivar. The longest roots (12.50 cm) were produced by Desiree potato cultivar grown on MS medium supplemented with 0.5 mgl-1 thiamin. Mozart potato cultivar performed better than Desiree cultivar in concern to mean length of shoots, number of leaves, number of roots and mean length of roots. No significant differences were found between the both cultivars in concern to the number of shoots and roots.